2019
DOI: 10.1212/nxg.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of cardiac involvement in mitochondrial myopathy

Abstract: ObjectiveOur goal was to perform a systematic review of the literature to demonstrate the prevalence of cardiac abnormalities identified using cardiac investigations in patients with mitochondrial myopathy (MM).MethodsThis systematic review surveys the available evidence for cardiac investigations in MM from a total of 21 studies including 825 participants. Data were stratified by genetic mutation and clinical syndrome.ResultsWe identified echocardiogram and ECG as the principal screening modalities that ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
0
31
1
2
Order By: Relevance
“…A few recent studies proposed that cardiac surveillance for mitochondrial patients can be stratified based on the clinical syndrome or phenotype alone. 7 8 30 However, such recommendations have limitations, given that the phenotype–genotype correlation is not always evident. For instance, CPEO and myopathy are common clinical features seen in adult patients with mitochondrial disease and the genetic causes are highly heterogeneous, which include primary mtDNA point mutations such as m.3243A>G, single, large-scale mtDNA deletions or multiple mtDNA deletions secondary to nuclear gene defects as outlined previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies proposed that cardiac surveillance for mitochondrial patients can be stratified based on the clinical syndrome or phenotype alone. 7 8 30 However, such recommendations have limitations, given that the phenotype–genotype correlation is not always evident. For instance, CPEO and myopathy are common clinical features seen in adult patients with mitochondrial disease and the genetic causes are highly heterogeneous, which include primary mtDNA point mutations such as m.3243A>G, single, large-scale mtDNA deletions or multiple mtDNA deletions secondary to nuclear gene defects as outlined previously.…”
Section: Discussionmentioning
confidence: 99%
“… 3–6 However, the spectrum of cardiac manifestation among patients with nDNA defects has only been described in isolated case reports or small case series. 7 At present, regular cardiac surveillance is routinely recommended for all patients with mitochondrial disease irrespective of the underlying genetic aetiology. 8 …”
Section: Introductionmentioning
confidence: 99%
“…mitochondrial disease (MD), can involve myocardium and induce cardiac dysfunction through disrupted mitochondrial respiratory chain functions [37]. In addition, even isolated cardiac phenotype is found in MD [38]. Thus, inherent but underdiagnosed MD might be included in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that patients with MELAS had significantly more electrocardiography and echocardiography (especially left ventricular hypertrophy) abnormalities than patients with other mitochondrial phenotypes. A common and well-described cardiac complication overrepresented in MELAS was Wolff–Parkinson–White syndrome (WPW) [ 28 ]. The worst prognosis can be independently predicted by a personal history of seizures and left ventricular hypertrophy in these patients [ 29 ].…”
Section: Clinical Picturesmentioning
confidence: 99%